Role of B7‐H3 in predicting response to neoadjuvant chemotherapy in muscle‐invasive bladder cancer - Ekamjit S. Deol; Reza Nabavizadeh; Roxane R. Lavoie; Mihai G. Dumbrava; Edlira Horjeti; Prabin Thapa; John C. Cheville; Igor Frank; Fabrice Lucien (BJUI Compass)
Abstract Background Neoadjuvant platinum‐based chemotherapy offers a modest survival advantage in muscle‐invasive bladder cancer (MIBC) for patients with pathologic response. B7‐H3 (CD276), an immune checkpoint overexpressed in various cancers, including urothelial‐cell carcinoma (UCC), has been associated with chemoresistance and poor oncologic outcomes. We aimed to explore if B7H3 expression on bladder biopsy samples was a predictive biomarker for pathologic response to neoadjuvant platinum‐based chemotherapy. Methods This was a retrospective cohort study among MIBC patients receiving neoadjuvant platinum‐based chemotherapy followed by radical cystectomy. All patients underwent routine preoperative biopsy of their tumour. Immunohistochemistry was used to evaluate B7‐H3 expression from pre‐operative specimens. The primary outcome of interest was pathologic complete response (pCR). Statistical analysis included Mann–Whitney U test, Fisher's exact test, Kaplan–Meier method, and Cox regression for survival analysis. Results Among 87 patients analysed, high B7‐H3 expression was found in 44.8% (n = 39) of patients. The median follow‐up periods were similar between the high and low B7‐H3 groups (high expression; 4.29 years [SD 3.04], low expression 3.94 years [SD 3.04], p = 0.60). Only 20.5% of patients with high B7‐H3 expression achieved pCR, compared to 41.7% in the low expression group (p = 0.04). Cox regression showed no significant differences in recurrence‐free or cancer‐specific survival between the high and low B7‐H3 expression groups (p > 0.05). Conclusion High B7‐H3 expression is associated with a reduced likelihood of achieving pCR in MIBC patients undergoing neoadjuvant chemotherapy. This suggests B7‐H3's potential as a predictive biomarker for chemotherapy response. Further research is needed to explore the role of B7‐H3 on platinum‐based chemotherapy response in urothelial cancer.